0137 The Falling Asleep Process in Adolescents. (12th April 2019) - de Zambotti, Massimiliano; Smith, Ellen; Goldstone, Aimee; Forouzanfar, Mohamad; Claudatos, Stephanie; Gil, Maureen; Alschuler, Vanessa; Lim, Yun Qi; Rosas, Leonardo; Prouty, Devin; Kardos, Lena; Colrain, Ian; et al.
Abstract: Introduction: Elevated bedtime psychophysiological activation interferes with the way people fall asleep and sleep. The falling asleep is an overlooked phenomenon, particularly relevant in the pathophysiology of insomnia. Insomnia disorder shows a profound sex difference in its prevalence, which emerges during adolescence. Greater vulnerability to insomnia in the female sex may be reflected in the manifestation of hyperarousal, particularly around sleep onset. Here, we compared the psychophysiology of the falling asleep process in adolescent boys and girls. Methods: 102 healthy adolescents (12-20y, 54 female) from the National Consortium on Alcohol and Neurodevelopment in Adolescence (NCANDA) SRI cohort underwent in-lab polysomnography (PSG). Cognitive (pre-sleep arousal scale), cortical (electroencephalographic, EEG) and cardiac (heart rate) arousal measures were analyzed before and across the wake-to-sleep transition (5min before and after sleep onset). Results: Approaching sleep onset was associated with a pronounced increase in EEG Delta and Theta power, while EEG Alpha, Sigma, and Beta power, as well as heart rate gradually dropped (p <.05). In the first 5min after sleep onset, EEG Delta and Beta power, and heart rate no longer changed, while Theta and Sigma power inverted their pattern and respectively, reduced and increased (p<.05). Girls tended to have higher heart rate and reduced EEG Alpha compared to boys, before sleep onset. Girls, compared to boys, had greater cognitive activation before bedtime (p<.05), and they took longer to fall asleep (21.3±17.4min vs. 14.8±14.5min; p<.05). Elevated pre-sleep cortical arousal (EEG-Beta power) was related to more PSG awakenings and %N2 sleep in girls, and to less %N3 sleep in girls and boys. Elevated cognitive activity was related to greater PSG wake after sleep onset and reduced %N3 sleep in boys. Conclusion: The falling asleep process is characterized by a progressive cortical synchronization and reduction in cardiac activation, which is similar in adolescent boys and girls, despite greater bedtime cognitive activation and delayed sleep onset in girls. Longitudinal data and manipulation of the pre-sleep arousal level are needed to ultimately unveil the role of the pre-sleep psychophysiological state on the falling asleep process and subsequent sleep. Support (If Any): NCANDA-grant:AA021696